PENGELOLAAN KOMPLAIN (KELUHAN) MASYARAKAT DALAM MEWUJUDKAN PEMERINTAHAN YANG BAIK DI KOTA SEMARANG - Wiyanto, Wiyanto (Prodi PPKn FKIP Universitas Pamulang, 2017)
The purpose of this study is to find out the problems that cause complaints, complaints management of society and business undertook Semarang city government to overcome obstacles in the management of community complaints in an attempt to realize good government in the city of Semarang. This research is a qualitative research. The research location is centered on Public Service Complaint Handling Center (P5) Semarang City. The source of data comes from the in-depth interviews conducted with employees P5, documents and questionnaires. Data were collected through interviews, documentation, and observation. To ensure the validity of the data the researchers used triangulation techniques and then performed the analysis. The results of this study indicate that the problem that raises the complaints in the community is the service both services and non-services from service providers (government of Semarang City) not in accordance with community expectations. In addition, complaints arise due to service providers and service users who violate the rights of other service users. Model of community resolving as an outcome of this research. Suggestion for government officials needs to pay attention and support the community to improve the services provided. For the next researchers who conduct an integrated academic study of various disciplines.